2022
DOI: 10.51698/aloma.2022.40.1.55-64
|View full text |Cite
|
Sign up to set email alerts
|

Uso de una aplicación de tableta personalizada para evaluar la comunicación en niños con TEA: AppTEA

Abstract: El uso de dispositivos digitales para tratar a personas con trastorno del espectro autista (TEA) tiene buena aceptación, pero hasta el momento no se han registrado investigaciones en Argentina que analicen empíricamente su aporte en cuanto a los comportamientos comunicativos. El objetivo de esta investigación consistió en evaluar la implicación de los dispositivos digitales por lo que respecta a dos parámetros conductuales: la postura y el foco atencional de niños con TEA. Para llevarlo a cabo se analizaron 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Lozano et al (2017) in a case study with a four-year-old with ASD found an increase in joint care after a seven-session intervention through educational applications on a digital tablet. In another study, Guzman et al (2022) found no difference in attention time when eleven children with ASD aged five to nine interacted with the AppTEA application or when they did not. (Pérez-Fuster et al, 2022).…”
Section: Joint Attentionmentioning
confidence: 91%
“…Lozano et al (2017) in a case study with a four-year-old with ASD found an increase in joint care after a seven-session intervention through educational applications on a digital tablet. In another study, Guzman et al (2022) found no difference in attention time when eleven children with ASD aged five to nine interacted with the AppTEA application or when they did not. (Pérez-Fuster et al, 2022).…”
Section: Joint Attentionmentioning
confidence: 91%